Titanocene(III) pseudohalides: an ESR and structural study - Křižan, Martin; Honzíček, Jan; Vinklárek, Jaromír; Růžičková, Zdeňka; Erben, Milan (Royal Society of Chemistry, 2014)
A series of complexes of the type [Ti(′Cp)2Y] {′Cp = η5-C5H5 (Cp), η5-C5H4SiMe3 (SiCp), η5-1,3-C5H3(Me3Si)2 (Si2Cp); Y = Cl−, CN−, NCS−, NCSe−, dicyanamide (dca), tricyanomethanide (tcm) and 1,2,3,4-thiatriazol-5-thiolate (ttt)} were prepared and studied by ESR spectroscopy. Ring-substituted compounds [Ti(SiCp)2Cl], [Ti(Si2Cp)2Cl], [Ti(SiCp)2CN] and [Ti(Si2Cp)2CN] dissolved in coordinating solvents exist in an equilibrium with solvated species. The thiatriazolthiolate ligand in complexes [Ti(′Cp)2(ttt)] behaves as a S,N-chelator to yield a thermally unstable 4-membered chelate ring having the ESR signal with significant splitting due to coupling with one 14N nucleus. Solutions of [Ti(′Cp)2Y] (Y = NCS−, NCSe−, dca and tcm) readily dissolve the additional pseudohalide salt giving anionic species [Ti(′Cp)2Y2]− with a characteristic ESR pattern caused by super-hyperfine splitting by two 14N nuclei. Cyanide complexes dissolve additional KCN as well, but no coupling to ligand nuclei (neither 14N nor 13C) was observed. The frozen-solution ESR spectra of [Ti(Si2Cp)2Cl], [Ti(Si2Cp)2CN] and [Ti(′Cp)2Y] (Y = NCS−, NCSe− and ttt) are typical for monomeric species of rhombic symmetry. The remaining complexes form dimeric {[Ti(Cp)2Cl]2, [Ti(SiCp)2Cl]2, [Ti(′Cp)2dca]2, and [Ti(′Cp)2tcm]2} or trimeric {[Ti(SiCp)2CN]3} adducts under these conditions. The nuclearity of [Ti(Cp)2CN] cannot be accurately determined by ESR spectroscopy due to its poor solubility but the presence of species with a higher spin ground state was confirmed (similar to the case of the above-mentioned dimers and trimer) by the observation of formally forbidden half-field transition. The reported results of the crystal structure analysis of [Ti(SiCp)2Cl], [Ti(Cp)2tcm], [Ti(SiCp)2tcm], [Ti(SiCp)2dca], [Ti(SiCp)2CN], and [TiCp2(NCS)]2O corroborate the findings based on spectroscopic measurements.